2014
DOI: 10.1016/j.stemcr.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Human Bone Marrow Stromal Cells Lose Immunosuppressive and Anti-inflammatory Properties upon Oncogenic Transformation

Abstract: SummaryBecause of their immunomodulatory properties, human bone marrow stromal cells (hBMSCs) represent promising stem cells for treatment of immune disorders. hBMSCs expansion precedes their clinical use, so the possibility that hBMSCs undergo spontaneous transformation upon long-term culture should be addressed. Whether hBMSCs retain immunosuppressive and anti-inflammatory properties upon oncogenic transformation remains unknown. Using sequentially mutated hBMSCs and spontaneously transformed hBMSCs, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…Using carboxyfluorescein succinimidyl ester (CFSE) dilution assays to monitor cell division, we found that AML-derived BM-MSCs suppressed the proliferation of phytohemagglutinin (PHA)-stimulated human peripheral blood mononuclear cells (PBMCs) irrespective of the molecular subgroup (Figure 3A). In line with previous studies, the level of immunosuppression (measured as non-proliferating PHA-stimulated lymphocytes) was 44% ± 20% and 14% ± 8% for HD-derived BM-MSCs and tMSCs, respectively (Figure 3A; Funes et al., 2007, Rodriguez et al., 2014, Sanchez et al., 2011). Intriguingly, AML-derived BM-MSCs had a more robust immunosuppressive potential (74% ± 18% for LR-AML, 55% ± 20% for IR-AML and 66% ± 16% for HR-AML; p < 0.05) than HD-derived BM-MSCs.
Figure 3In Vitro Immunosuppressive and Anti-Inflammatory Properties of BM-MSCs from HDs and AML Patients(A) Left: level of immunosuppression measured as percentage of CFSE + non-proliferating cells.
…”
Section: Resultsmentioning
confidence: 99%
“…Using carboxyfluorescein succinimidyl ester (CFSE) dilution assays to monitor cell division, we found that AML-derived BM-MSCs suppressed the proliferation of phytohemagglutinin (PHA)-stimulated human peripheral blood mononuclear cells (PBMCs) irrespective of the molecular subgroup (Figure 3A). In line with previous studies, the level of immunosuppression (measured as non-proliferating PHA-stimulated lymphocytes) was 44% ± 20% and 14% ± 8% for HD-derived BM-MSCs and tMSCs, respectively (Figure 3A; Funes et al., 2007, Rodriguez et al., 2014, Sanchez et al., 2011). Intriguingly, AML-derived BM-MSCs had a more robust immunosuppressive potential (74% ± 18% for LR-AML, 55% ± 20% for IR-AML and 66% ± 16% for HR-AML; p < 0.05) than HD-derived BM-MSCs.
Figure 3In Vitro Immunosuppressive and Anti-Inflammatory Properties of BM-MSCs from HDs and AML Patients(A) Left: level of immunosuppression measured as percentage of CFSE + non-proliferating cells.
…”
Section: Resultsmentioning
confidence: 99%
“…In order to recapitulate a BM stroma milieu, 1 × 10 5 HL60 (n = 31 mice) or MOLM-13 (n = 33 mice) cells were intra-BM transplanted into non-irradiated NSG mice together with 3 × 10 5 irradiated BM-MSCs. 25,27 HL60 AML grafts were monitored by BM aspiration and mice were randomized into treatment groups when graft was >1% in the contralateral BM (~2–3 weeks post-transplant). For MOLM-13 AML grafts, mice were randomized for treatment 3 days after intra-BM transplant due to its aggressiveness.…”
Section: Methodsmentioning
confidence: 99%
“…It is thought that MSCs respond to inflammation and have specific roles in immune regulation, lymphopoiesis, and bone homeostasis [70,71]. These reports used cultured MSCs; accordingly, it is unknown whether the response is similar under physiological conditions.…”
Section: Msc Lineage Tracking In Vivomentioning
confidence: 99%